Characterisation of Atropine in High Aqueous Dilutions for Homeopathic Use - Cruces-García, Miguel A.; Ramírez, Verónica Ivonne Hernández; Rangel-López, Edgar; Martínez, Edgar Fernando Cortés; Velázquez-Domínguez, José Antonio (Homœopathic Links, 2020)
Background Atropine is a constitutive alkaloid of belladonna, which is widely used in homeopathic medicine in high dilutions (HDs). In HDs, atropine molecules are not correlated with the energy of electrophysical interactions or the presence of aggregates, resulting in neurotoxic effects. However, in small concentrations at the nanoscale, its effects could present therapeutic advantages.Objective In the present study, the physicochemical properties of a range of HDs of atropine were analysed to establish a correlation between its electrical and morphological properties.Methods The electrodynamic properties were analysed with a conductivity meter, whereas the size and morphology of the nanoparticles were evidenced by transmission electron microscopy and atomic force microscopy. The HDs were prepared with deionised water under sterile conditions. Hydrogen potential (pH) and electrical potential were determined with a portable equipment. Electrical conductivity (EC) was calculated using the ionic strength and Debye length.Results The characterisation of atropine HDs showed the formation of aggregates and the fluctuation of morphological variables at each dilution. Electromagnetic and pH changes were evidenced, which could contribute to a change in the EC. Possibly being responsible for a better response at the cellular level without triggering side effects in the individual.These data suggest that the forces of Derjaguin–Landau–Verwey–Overbeek and the forces of Van der Waals are involved in the variety of forms among these aggregates.The EC was significant at 200°C. This variation suggests changes in the electromagnetic configuration of the HDs. It is only through the conformation of nanoparticle aggregates that these variations can be triggered.Conclusion Atropine HDs have demonstrated the presence of nanoparticle aggregates with different morphological and electromagnetic properties. Our results may be relevant for future approaches focused on the use of atropine in HDs to minimise cytotoxic effects or modulate adverse effects in patients with neuropathy.Until now, the therapeutic effects of homeopathy have not been relevant to the scientific community; however, here we demonstrate with scientific approaches the conformation of aggregates of nanoparticles present in HDs that modify their structure and electromagnetism, properties that could produce differential biological responses without generating cytotoxicity.
Keywords: atropine; high dilutions; homeopathic use; neuropathy